Impact of microwave disinfestation treatments on the bacterial communities of no‐till agricultural soils. (20th August 2019) - Khan, Muhammad J.; Jurburg, Stephanie D.; He, Jizheng; Brodie, Graham; Gupta, Dorin
Abstract: Growing herbicide resistance has encouraged the development of new technologies for weed control. Microwave (MW) heating of soil before sowing has been shown to reduce weed establishment in no‐till farming systems and substantially increases crop productivity. However, the effect of this technology on the soil microbial community in general, and on beneficial soil microbes such as ammonia oxidizers in particular, warrants further study. In order to check the effect of MW soil disinfestation treatments on the soil biota, indigenous soil microcosms were treated under a horn antenna of the MW prototype for three distinct durations. Immediately after heating (T0) and 28 days after heating (T28) the soil was collected at two penetration depths (0–5 and 5–10 cm) of MW energy to determine the bacterial community responses based on 16S rRNA amplicon sequencing and the total abundances of bacteria and ammonia oxidisers with qPCR. Although total bacteria and ammonia oxidizer abundances exhibited no response to the MW treatments, bacterial community composition differed according to the treatment durations. Community responses clustered into two categories: no effect at low heating intensities (0 and 30 s, 17–45°C) and strong effect at high heating intensities (60 and 90 s, 65–78°C). For the latter group, community richness did not recover to its pre‐heating levels within the 4 weeks studied. Immediately after high heating intensity treatments, the relative abundance of Firmicutes increased and that of Proteobacteria decreased significantly regardless of penetration depth. The relative abundances of beneficial soil microbes ( Micromonosporaceae, Kaistobacter and Bacillus ) were significantly higher as soils recovered from high heating intensities compared with untreated soils at T28. Our findings suggest that although pre‐sowing MW treatments alter the soil microbial community, beneficial soil microbes exhibit faster recovery. Highlights: High heating intensities reduced bacterial community richness that did not recover to pre‐heating condition. Heat resistant bacterial taxa survived high heating intensities < 28 days after heating regardless of penetration depth. High‐intensity heating did not induce a negative impact on the abundance of ammonia‐oxidizing bacteria and archaea. Relative abundances of dormant heat‐resistant beneficial taxa exhibited recovery after 28 d.